Answer:
c) -x^3 + x^2 - 1
Step-by-step explanation:
Given: u (x) = x^5 - x^4 +x^2 and v(x) = -x^2
(u/v)(x) = u(x)/v(x)
Now plug in the given functions in the above formula, we get
= (x^5 - x^4 + x^2) / -x^2
We can factorize the numerator.
In x^5 - x^4 + x^2. the common factor is x^2, so we can take it out and write the remaining terms in the parenthesis.
= x^2 (x^3 - x^2 + 1) / - x^2
Now we gave x^2 both in the numerator and in the denominator, we can cancel it out.
(u/v)(x) = (x^3 - x^2 + 1) / -1
When we dividing the numerator by -1, we get
(u/v)(x) = -x^3 + x^2 - 1
Answer: c) -x^3 + x^2 - 1
Hope you will understand the concept.
Thank you.
Answer:
sin b = 0.8
Step-by-step explanation:
Since a and b are complementary angles , then
sin b = cos a = 0.8
Answer:
1
Step-by-step explanation:
hope this help:) I use slop formula
Answer:
slope intercept form
Step-by-step explanation:
X+y = 42
x-y = 8
x = 8+y
Substitute it in 1st equation,
8+y+y=42
2y = 34
y = 17
Substitute it in 1st eq.,
x = 42-17 = 25
So, the two numbers are 25 & 17
Hope this helps!